Nesting materials for does: effect on nest building and performance in the first parturition - de Oliveira, Maria C.; Lima, Sarah C. O.; Mesquita, Sabina A.; Silva, Jessica A.; Gomes, Yeury S.; Attia, Youssef A.; Oliveira, Higor C. (Revista Colombiana de Ciencias Pecuarias, 2017)
Background: The material placed into the nest should provide comfort to both does and their kits. Objective: To evaluate the effect of different nesting materials on rabbit doe performance and nest building. Methods: Thirty primiparous rabbit does were randomized allotted in a block design with three treatments and ten replicates each. The treatments consisted of nest bedding with wood shavings (280 g, control), Tifton hay (220 g), and thin strips of newspaper (200 g). The state of the nest was assessed to evaluate mixing of the material with doe’s hair and preservation of the original material. Kit body weight, daily weight gain, and survival rate were evaluated from birth to weaning. Results: The nesting material did not affect the mixing level of material and hair, amount of hair in the nest, body weight, daily weight gain, or survival rate of rabbits from birth to 35 d of age (p > 0.05). However, preservation of original material in the nest was lower when Tifton hay was used (p < 0.05). Correlations between material type and total number of born alive and the amount of hair, mixture level between hair and material, and material preservation in the nest were not significant (p > 0.05). No correlation (p > 0.05) was observed between material preservation and hair presence or mixture level between both. Positive correlation between hair presence and mixture level (p < 0.001) was observed. Conclusion: Tifton hay and cut newspaper can be used as nest bedding for pregnant does in replacement of wood shavings, with no negative effects on nest building behavior or kit performance.